The Mediating Function of Islamic Work Ethics in the Association Between Ethical Leadership and Job Performance in Islamic Hospitals - Nijwah, Izzah Sarirotun; Achmad, Affan Wazzar; Mukhlisin, Ahmad (Ekonomi Syariah IAIN Kudus, 2025)
This study examines how healthcare professionals' performance in Islamic hospitals after the COVID-19 epidemic is affected by Islamic Work Ethics (IWE) and Ethical Leadership. Descriptive statistical analysis and a quantitative approach were employed in this study. A stratified random sample of healthcare professionals from Kudus Regency's Islamic hospitals was collected. A total of 157 respondents completed a standardized questionnaire that was used to gather the data. The suggested linkages and data analysis were tested using SmartPLS. This study found that IWE and ethical leadership significantly impact healthcare professionals' job performance. Furthermore, ethical leadership positively affects the IWE, and the IWE partially mediates the relation between ethical leadership and job performance. Only healthcare professionals working in Kudus, Jawa Tengah's Islamic hospitals, are included in this study. Therefore, future studies may involve experts from a larger range of industries to obtain a more comprehensive understanding. This study presents a fresh viewpoint by investigating the concurrent relationship between IWE, job performance, and ethical leadership in Islamic hospitals. Additionally, this study focuses on Islamic hospitals, which uniquely integrate Islamic values into workplace practices, especially in the post-pandemic era.